Carnalidade e libertação: a dimensão erótica a partir da Filosofia da Libertação de Enrique Dussel - Souza, Luis Fernando de Carvalho (2018)
The theme of the research was the erotic and carnal (corporal) liberation from the thought of Enrique Dussel. The relevance of the research is justified primarily as a theme that Dussel addressed in his Philosophy of Liberation emphatically in the 1970s, not exploring it later in the course of his work, which constitutes an internal redemption in the work of the author. The social relevance that the work brings is related to the world reality faced by men, transsexuals, lesbians and people in general who are oppressed by the exclusionary and heteronormative chauvinist system. The central problem of the research was: how from the carnality (corporal relation) can one project the liberation? The development took place in four chapters that sought to embrace the problematic, at different times laying the groundwork to answer it. The methodology used was the bibliographical research of the Philosophy of Liberation, feminist thought and distinct corporeal identities. The first chapter aimed, through Dussel's methodology, to establish an analytical starting point (starting from the victim of the erotic relation) in order to project its liberation. Already in this chapter the approach of eroticism occurred beyond the man-woman relationship (predominant in Dusselian thought). The second chapter aimed to trace a history of Dussel's thinking about erotica, specifically, in the male-female relationship. The separation was done for didactic purposes, since, there are specifics in affective relationships that can not be treated under the same nickname. Some questions are hormonal, psychic or biological have their specifics, and therefore need to be worked in different ways. The third chapter dealt with the material ethics of Dussel, widely discussed in Ethics of Liberation (1998). As the theme of research is erotic the content of ethics has been worked around the flesh (body) in relationships involving erotica. Initially the formation of ethical and moral conscience was distinguished from the biological and neurological exposition that Dussel made in the first hundred pages of the work. Then it was tried to treat how the body constitutes itself as content of the ethics and which the ways for its liberation. The last chapter dealt, for the most part, with homosexual erotic in some of its variants and the relation that Dussel established with the feminist thought, especially, of years 1960-70. The consideration of feminism was only an appendix which sought to warn of the danger that in the name of the rupture with an oppressive Totality one might construct another equally oppressive Totality. In the case of homosexual erotic some relationships were punctuated from their specificities and it was noticed that the question is object of several discussions that gain different day to day, so much that, in what matter of months or of few years some approaches or categories have become obsolete and / or have reached new contours. It was concluded that the carnal liberation begins by the awareness of the victim of oppression from its distinction in relation to the oppressive heteronormality.